Penentuan Lama Sulfonasi pada Proses Produksi Surfaktan Mes untuk Aplikasi EOR - Mira Rival; Tun Tedja Irawadi; Ani Suryani; Dwi Setyaningsih; Erliza Hambali (Institut Pertanian Bogor, 2011)
For producing oil remains that remained at old oil wells (mature field), a method of advanced oil acquirement improvement known as an Enhanced Oil Recovery (EOR) should be applied. Surfactant plays an important role in EOR process by reducing interfacial tension (1FT), altering wettability, reducing oil viscosity, and stabilizing dispersion to facilitate the process of oil jetting from reservoir to production well. To optimally cleanse oil that still remained a surfactant compatible with formation water and reservoir is needed. This study was conducted to get the best time of sulfonation process for producing MES surfactant with lower interfacialtension for EOR application. Results showed that the best times of sulfonation process with lower interfacial tension value were 3 and 4 hours.